2010
DOI: 10.1109/tmag.2010.2044374
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular Magnetic Anisotropy in CoFeB/Pd Bilayers

Abstract: Perpendicular magnetic anisotropy is observed in ultrathin ( 0.6 nm) amorphous Co 40 Fe 40 B 20 when sputtered on an MgO (001) buffer layer and capped with Pd. The layers are superparamagnetic with a blocking temperature of 230 K, below which they show an exponential temperature dependence of coercivity. Perpendicular magnetic anisotropy is observed in the as-deposited state and the mechanism is different from that of CoFeB/Pt, which requires postannealing. These ultrathin layers could be a model system for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
2
18
2
Order By: Relevance
“…[2][3][4][5][6][7][8] However, the results in this article (and some recent papers) [26][27][28] have demonstrated that the structural condition is not a necessary criterion for the CoFeB/Pd interfaces. This is presumably a physically interesting aspect for a deep analysis of interfacial magnetic moment and electronic structure of the CoFeB/Pd interfaces by a number of tools, e.g.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8] However, the results in this article (and some recent papers) [26][27][28] have demonstrated that the structural condition is not a necessary criterion for the CoFeB/Pd interfaces. This is presumably a physically interesting aspect for a deep analysis of interfacial magnetic moment and electronic structure of the CoFeB/Pd interfaces by a number of tools, e.g.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…[23][24][25] Recently, PMA in multilayer films using amorphous CoFeB layers and noble metal spacing have been reported. [26][27][28] Several advantages allow considering PMA amorphous CoFeB films as an excellent candidate for spin-transfer torque applications:…”
Section: Introductionmentioning
confidence: 99%
“…This is evidence [73] that the anisotropy of a single Pd/CoFeB/Pd multilayer is given by the combination of an in-plane volumetric component K v , and an out-of-plane component K s , which arises from a surface or interface anisotropy present at each CoFeB/Pd interface due to atomic mixing [54,74,75]. This competition eventually leads to the disappearance of the PMA for thicker CoFeB layers, as shown in Fig.…”
Section: Cofeb Thicknessmentioning
confidence: 75%
“…20 However, the well established layer by layer growth of the bottom Co/Ni ML on a smooth (111) textured Pt buffer 21 has to be compared with the island-like growth process of the top ML on a Al 2 O 3 oxide barrier. 22 Moreover, the top ML may not be well (111) textured on the amorphous barrier, and it has been found that (100) and (110) grain significantly reduce PMA in Co/Ni ML. 23 The tail of the first magnetization jump is typical of the dipolar interactions (so-called demagnetization field) in PMA film thicker than few nanometers 24 but that a fully anti-parallel state is reached before the second step.…”
Section: Experimental Methodsmentioning
confidence: 99%